2021
DOI: 10.1029/2020jf005848
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Topography, Bedrock Weathering, and Water Storage Across a Sequence of Ridges and Valleys

Abstract: Bedrock weathering regulates nutrient mobilization, water storage, and soil production.Relative to the mobile soil layer, little is known about the relationship between topography and bedrock weathering. Here, we identify a common pattern of weathering and water storage across a sequence of three ridges and valleys in the sedimentary Great Valley Sequence in Northern California that share a tectonic and climate history. Deep drilling, downhole logging, and characterization of chemistry and porosity reveal two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(99 citation statements)
references
References 92 publications
8
87
4
Order By: Relevance
“…Of the variables we assessed, the strongest predictor of chemical and physical weathering, and by extension rock strength, is the location of the rockmass with respect to ridge‐channel topography. This result is consistent with previous studies that have observed the deepest subsurface extent of chemically altered and fractured rock under ridges and thinnest extent under valley bottoms (Pedrazas et al., 2021; St. Clair et al., 2015). The two leading mechanisms invoked to explain this pattern are a topographic stress control on bedrock fractures (Moon et al., 2017; Slim et al., 2015; St. Clair et al., 2015), and the subsurface topography of the water table (Rempe & Dietrich, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of the variables we assessed, the strongest predictor of chemical and physical weathering, and by extension rock strength, is the location of the rockmass with respect to ridge‐channel topography. This result is consistent with previous studies that have observed the deepest subsurface extent of chemically altered and fractured rock under ridges and thinnest extent under valley bottoms (Pedrazas et al., 2021; St. Clair et al., 2015). The two leading mechanisms invoked to explain this pattern are a topographic stress control on bedrock fractures (Moon et al., 2017; Slim et al., 2015; St. Clair et al., 2015), and the subsurface topography of the water table (Rempe & Dietrich, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Of the variables we assessed, the strongest predictor of chemical and physical weathering, and by extension rock strength, is the location of the rockmass with respect to ridge-channel topography. This result is consistent with previous studies that have observed the deepest subsurface extent of chemically altered and fractured rock under ridges and thinnest extent under valley bottoms (Pedrazas et al, 2021;St. Clair et al, 2015).…”
Section: Variations In Weathering With Respect To Ridges Channels And...supporting
confidence: 94%
“…As noted by Pedrazas et al. (2021), air photos indicate that the modern woody plant community distribution has persisted since at least 1937. The blue oaks are mature (most likely >100 years old), with very few seedlings or saplings.…”
Section: Methodsmentioning
confidence: 75%
“…Hatching showing zone of discrete fractures is meant to delineate the depth extents and not actual strike/dip of fractures. Fractures are typically either high angle (60–80° dip) oriented at a strike of approximately 97° or low angle (30–40° dip) fractures oriented at a strike of approximately 172° (right‐hand rule convention (Pedrazas et al., 2021). Figure modified from Pedrazas et al.…”
Section: Methodsmentioning
confidence: 99%
“…These aspects of weathering the bedrock are explained in detail by [38]. The presence of faults/discontinuities at the base of the weathering profile can also affect the hydraulic conductivity and have a major influence on the groundwater flow systems by affecting their hydraulic conductivity [36].…”
Section: Discussionmentioning
confidence: 99%